Flowability and Strength Characteristics Based on Replacement Rate of Admixture Material for Modified Sulphur Mortar - Lee, Sangsoo; Song, Hayoung; Jung, Byeongyeol (Asian Journal of Chemistry, 2014)
This study compared the flowability and strength characteristics of mortar based on the replacement rate of fly ash, silica fume and blast furnace slag which were the admixture materials for the modified sulphur mortar. The flowability increased when the admixture material was substituted for the modified sulphur mortar. The silica fume showed the highest strength in terms of flexural strength and compressive strength, followed by the blast furnace slag and fly ash.